SWARMORPH: Multirobot Morphogenesis Using Directional Self-Assembly - O'Grady, Rehan (2013)
In this paper, we propose SWARMORPH: a distributed morphology generation mechanism for autonomous self-assembling mobile robots. Self-organized growth of global morphological structures emerges through the repeated application of local morphology extension rules. We present details of the directional self-assembly mechanism that provides control over the orientation of interrobot connections. We conduct real-world experiments to validate the low-level directional self-assembly mechanism and the growth of global morphologies. We demonstrate the scalability of the approach with large numbers of robots in simulation-based experiments.